Impact of the Sunshape Variability on the Performance of a Central Receiver System. (May 2015) - Delgado, A.; Ron, R.; Blesa, E.; Hidalgo, C.; Gertig, C.
Abstract: DNV GL found that several parameters with impact on CSP plant performance are often not taken into account properly in Due Diligence processes. This paper investigates the potential impact of one of them. The purpose of this paper is the evaluation of the incident flux on the receiver system due to the variability of the Sunshape and the analysis of the potential benefits of implementing dynamic Sunshape profiles into simulation software to increase accuracy. The work includes an analysis of plant and spillage efficiency for various instants of the year using an optical model developed in DNV GL for a site near Seville, Spain. External cylindrical and cavity receivers have been considered during this study with state-of-the-art plants designs. Resulting: efficiencies from simulations with static and dynamic Sunshape profiles have been compared and the differences at each DNI level applied to the annual DNI time series to give a preliminary estimation on the impact on annual intercepted energy. It has been found that an underestimation of spillage losses of around 5% can be expected for both receiver types at the chosen site, when simulating with static Sunshape profiles instead of dynamic Sunshape profiles correlated with the DNI measured at ground level. Since the spillage losses themselves only contribute to about 5-10% of the overall losses, the impact of up to 0.5% of the annual energy is not significant compared to other parameters, e.g. the atmospheric attenuation.